Contribution of Certification and School Climate Allowances to The Motivation of Teacher Work in the Middle School District of Kinali, West Pasaman Regency - Lusiana, Lusiana; Rukun, Kasman; Yahya, Yahya (International Journal for Educational and Vocational Studies, 2019)
The objectives of this study are (1) Contribution of certification to teacher work motivation, (2) Contribution of the school climate to teacher work motivation, (3) Contribution of certification allowances and school climate together to work motivation. This type of research is quantitative correlational in nature, the population in this study were all junior high school teachers in Kinali sub-district with the status of civil servants with a population of 107 people, a sample of 30 people taken using the startified proportional random sampling technique. Data collection techniques using questionnaires, data analysis techniques (1) description of data, (2) testing requirements analysis and (3) testing hypotheses. The results of the study prove that (1) There is a contribution of certification to work motivation because certification contributes 25.6% to the teacher's work motivation (2) the school climate contributes 28.3% to the teacher's work motivation (3) certification and the school climate together contribute 37.5% to the motivation of the teacher's work. Suggestions that can be put forward based on the findings to improve the work motivation of the teacher are expected that the principal can provide certification allowances to teachers who meet the requirements. To increase the work motivation of teachers, it is necessary to fix the low school climate, the Supervisors to provide a school climate of cooperation with teachers in accordance with technological developments. The education office's policy in terms of managing learning in schools should aim at increasing certification allowances.